Software and methodological support for training specialists in the field of "fitness - boxing": Theory and practice - Rakovetskiy, A.I.; Ponomarev, V.V.; Malinin, A.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to theoretically substantiate, develop software and methodological support for training fitness-boxing specialists, and recommend it for practical use. Methods and structure of the study. The theoretical and programmatic-methodological support for the organisational and pedagogical conditions for training fitness-boxing specialists was formed and developed at the Russian State Agrarian University - Moscow Timiryazev Agricultural Academy from 2023 to 2025. 45 teachers and more than 300 students participated in the formation of scientific and practical material. The following research methods were selected to collect factual material: analysis of scientific and methodological literature, surveys, interviews, questionnaires; modelling, expert assessments, observation, preliminary pedagogical research, abstraction, systematisation, methods of mathematical statistics, etc. The compiled and systematised scientific and methodological material contributed to the development of a new direction in the professional training of physical culture and sports specialists – ‘fitness-boxing’ as a sports-applied and physical culture and health direction for active and systematic training of all social groups of the country's population. Results and conclusions. Scientific and theoretical research and preliminary practical work have contributed to the development of software and methodological support for training specialists in the field of fitness-boxing, which makes it possible to expand the content and areas of training, retraining and professional development for specialists, coaches, teachers, educators and instructors in the field of ‘Physical Culture and Sport.’ In addition, rules for fitness-boxing competitions have been developed to improve sports and applied skills, increase the popularity and attractiveness of this modern form of physical activity, which integrates various dance rhythms and movements with elements of boxing exercises. This helps people who do it to be ready to be modern, active, and protected.